GOLD MINERS SOCIOECONOMIC CHANGE IN THE DISTRICT IV NAGARI KOTO TUO SIJUNJUNG DISTRICT OF WEST SUMATERA. THESIS. SOSIOLOGI OF EDUCATOIN STUDIES PROGRAM COLLEGE OF TEACHER TRAINING AND ADUCATION (STKIP PGRI) WEST SUMATERA PADANG.2014 - Alhamra, Bobi; Aziwarti, Aziwarti; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
Thesis examines the gold mining in Nagari Koto Tuo opportunities most people to change the standard of living for the better , giving the new changes in the lives of the people on the other negative impacts on the health hazards . The goal is achieved in this study was to describe :